Use of Commercial MALDI‐TOFs for Analyte Quantification by a Newly Invented Method. (19th May 2016) - Park, Kyung Man; Yoon, Sohee; Moon, Jeong Hee; Lee, Seong Hoon; Kim, Myung Soo
Abstract : As part of the recently developed quantification method using matrix‐assisted laser desorption ionization, matrix ion abundances are used to control the effective temperature, to construct a calibration curve, and to check the reliability of the quantification results. This method has not been used with commercial instruments owing to the difficulties in measuring the matrix ion abundances. In this work, we present a modification of each of the above guidelines to allow for quantification with commercial instruments. The modified method works with commercial instruments, which is partial proof for the validity of the method. Abstract :